2006
DOI: 10.1016/j.exer.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin as a novel locally produced relaxing peptide of the iris sphincter and dilator muscles

Abstract: Ghrelin is a recently described acylated peptide, which works as a somatosecretagogue and has described effects on the smooth, skeletal and cardiac muscle. We examined the production and effects of ghrelin on relaxation of the iris muscles. Contractile effects of 1e5 human ghrelin (frGhr, 10 À9 À6 Â 10 À5 M) and 1e5 human des-octanoyl-ghrelin (d-frGhr; 10 À9 À6 Â 10 À5 M) were tested on iris rabbit sphincter (n ¼ 11 frGhr; n ¼ 7 d-frGhr), dilator (n ¼ 6 frGhr; n ¼ 6 d-frGhr) and rat sphincter (n ¼ 6 frGhr; n ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 48 publications
0
36
1
Order By: Relevance
“…Des-acyl ghrelin does not influence sleep, memory, behavior nor milk secretion [21,108,154]. Relaxing effects of des-acyl ghrelin in iris sphincter muscle were similar to those of ghrelin, while in dilator muscle, des-acyl ghrelin did not significantly alter active tension and the relaxing effect of ghrelin was blunted by GHSR-1a blockage [122].…”
Section: Other Effectsmentioning
confidence: 78%
See 1 more Smart Citation
“…Des-acyl ghrelin does not influence sleep, memory, behavior nor milk secretion [21,108,154]. Relaxing effects of des-acyl ghrelin in iris sphincter muscle were similar to those of ghrelin, while in dilator muscle, des-acyl ghrelin did not significantly alter active tension and the relaxing effect of ghrelin was blunted by GHSR-1a blockage [122].…”
Section: Other Effectsmentioning
confidence: 78%
“…The continuously increasing list includes stimulation of prolactin, ACTH, AVP [103,106], promotion of slow-wave sleep [154], memory retention and anxiety-like behavior [21] and stimulation of milk secretion [108]. Recently, we have reported that ghrelin is expressed in the iris and induces relaxation of iris sphincter and dilator muscles [122]. Des-acyl ghrelin does not influence sleep, memory, behavior nor milk secretion [21,108,154].…”
Section: Other Effectsmentioning
confidence: 99%
“…Both acylated and non-acylated forms of ghrelin can mediate some of ghrelin effects while only the acylated form can bind to GHSR-1a. The activation of cyclooxygenase by non-acylated, acylated and truncated forms of ghrelin indicates the existence of another active receptor different from GHSR-1a [10,[46][47][48]. CD36, a multifunctional B-type scavenger receptor expressed in the adipose tissue, platelets, monocytes, macrophages, denditric cells, microvascular endothelium and myocardium [49], is implicated in ghrelin's role in the protection of the myocardium from ischemia [50].…”
Section: Ghrelin Receptorsmentioning
confidence: 99%
“…Ghrelin is also produced in the X/A cells of the intestine and in some others tissues such as the pancreas, kidney, placenta, lymphatics, *Address correspondence to this author at the Department of Physiology, Faculty of Medicine, Alameda Professor Hernâni Monteiro, 4200-319 Porto, Portugal; Tel: +351 225513644; Fax: +351 225513646; E.mail: arsousa@med.up.pt # Both authors had the same contribution to the article gonads, adrenal, thyroid gland, heart, lung, pituitary, hypothalamus, eye [10], human B-and T-lymphocytes, neutrophils [1,[10][11][12], morula, blastocyts and embryos [13]. Ghelardoni observed that ghrelin gene expression and its protein were, in some tissues, dissociated [14].…”
mentioning
confidence: 99%
“…Ghrelin is a novel growth hormone released mainly from the stomach (9). It is involved in food intake, regulation of appetite and energy homeostasis, in addition modulation of gastrointestinal, cardiovascular, pulmonary and immune functions, cell proliferation/apoptosis (10).…”
mentioning
confidence: 99%